2020
DOI: 10.1155/2020/8645343
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Up Operational Performance of Manufacturing Organizations through Interpretive Structural Modelling of Enabling Practices

Abstract: For achieving world-class performance and competitiveness in today’s global highly complex environment and competition, there is an immense pressure on manufacturing organizations having limited resources to pursue operational excellence in terms of productivity and quality, reduce cost, and provide high-quality products in shorter lead times. Identification of representative practices affecting operational performance (OP) and understanding of mutual dependence among those practices will improve the performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
2
5
0
Order By: Relevance
“…The significant effects imply that by placing focus on HRM, LM and OC, manufacturing organizations can boost the successful implementation of TQM and SCM practices. The results established are consistent with previous studies [85]. For example, Dubey and Singh [29] concluded that the relationship between LM and TQM is significant which endorses H 1 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The significant effects imply that by placing focus on HRM, LM and OC, manufacturing organizations can boost the successful implementation of TQM and SCM practices. The results established are consistent with previous studies [85]. For example, Dubey and Singh [29] concluded that the relationship between LM and TQM is significant which endorses H 1 .…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, LM, HRM and OC can significantly enhance PI as shown in Table 6. These analytical results of direct effects are consistent with those obtained by [5,20,25,85]. Furthermore, it was found from the bootstrapping technique that 21% to 37% effects of LM, HRM and OC on PI were explained through TQM and SCM.…”
Section: Discussionsupporting
confidence: 88%
“…Warfield (1974) proposed the ISM technique to capture the complex interrelationships of emerging socio-economic factors. ISM is an interactive technique used by research groups in complex environments as a communication mode to transfigure ambiguous and equivocal mental models of systems into a well-defined and explicit hierarchical model (Alawamleh & Popplewell, 2011 [ 80 ]. ISM has been broadly utilized in the early literature on policymaking to its wide use in recent research [ 81 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, this clubbed analysis is helpful to differentiate the input, output and intermediate parameters [ 85 ]. The elements are categorized into four clusters depending upon their driving power and dependence: Autonomous, Dependent, Linkage and Independent [ 80 ].…”
Section: Methodsmentioning
confidence: 99%
“…Manufacturing companies are struggling to achieve excellence in their operations in terms of improved quality, productivity, and reduced cost. The Covid-19 pandemic has further aggravated the lacklustre operational performance due to unavailability of personnel, the crisis in the workforces' mental, physical and social dimensions along with lack of resources ( Arshad Ali et al, 2020 ). Lack of operational performance is one of the major concerns that need to be alleviated in manufacturing industries in this covid era.…”
Section: Theoretical Backgroundmentioning
confidence: 99%